(untitled) (Texas Journal of Engineering and Technology, 2022)
Pore or formation pressure calculation is crucial to petroleum industry. There is currently no widely accepted approach for pore pressure estimation in carbonate reservoirs, and the results are still far from satisfactory. In this study, discussion two approaches called Eaton Slowness and Bowers Original method utilizing in prediction pore pressure. The concerned data (logs, calibration data, drilling, and mud report) and these data were utilized in Techlog 2015 software. Pore pressure in the Tanuma formation is around 4650 psi according to the Eaton data, compared to 3100 psi for the Bowers technique. Eaton’s hypothetical mud weight at a certain depth was greater than the actual mud weight, however bowers’ results showed that it was lower than the actual mud utilized for this well. When the results of two methods compared against mud weight and the pressure tests are both yield agreeable. Even with improved knowledge, the characteristics for reservoir formations may be was the impact of porous systems on velocities and numerous correlation aspects are still poorly understood. The Bowers method of pore pressure computation is substantially more accurate than the Eaton method.